2017
DOI: 10.3390/su9040534
|View full text |Cite
|
Sign up to set email alerts
|

A Geo-Event-Based Geospatial Information Service: A Case Study of Typhoon Hazard

Abstract: Social media is valuable in propagating information during disasters for its timely and available characteristics nowadays, and assists in making decisions when tagged with locations. Considering the ambiguity and inaccuracy in some social data, additional authoritative data are needed for important verification. However, current works often fail to leverage both social and authoritative data and, on most occasions, the data are used in disaster analysis after the fact. Moreover, current works organize the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Some of the most active social networking sites, such as Twitter, WhatsApp, WeChat, Instagram, Youku, and YouTube, provide people free access to personal information, including text messages, location, and social relationships. All of these features have resulted in the inclusion of Twitter/WeChat and other social media in crisis management studies (Zhang, Wu, Wang, & Su, 2017). Therefore, creating visualization and representation platforms for partnering people and various sectors to support the disaster management process can improve the understandability of rescue and relief assessment plans.…”
Section: Related Work: Progress and Challengesmentioning
confidence: 99%
“…Some of the most active social networking sites, such as Twitter, WhatsApp, WeChat, Instagram, Youku, and YouTube, provide people free access to personal information, including text messages, location, and social relationships. All of these features have resulted in the inclusion of Twitter/WeChat and other social media in crisis management studies (Zhang, Wu, Wang, & Su, 2017). Therefore, creating visualization and representation platforms for partnering people and various sectors to support the disaster management process can improve the understandability of rescue and relief assessment plans.…”
Section: Related Work: Progress and Challengesmentioning
confidence: 99%
“…Such methods rely on the ability to determine the geographic area referred to by spatial relation terms in everyday language. For example, computational extraction of geographic content from text (e.g., extraction of disease, disaster impact, or environmental data from social media) can incorporate models for spatial relation terms to more accurately locate phenomena (Bassi, Manna, & Sun, 2016; Zhang, Wu, & Su, 2017). In locations where many languages are spoken, a multilingual approach provides access to larger amounts of data that are more representative of the population, better supporting current machine learning models.…”
Section: Introductionmentioning
confidence: 99%
“…It proved that users tend to share their status during a crisis on the social network, indicating the potential of social networks for a quick damage assessment. Research has shown that the severity of damage in a region was correlated with the amount of crisis-related activities in the social network in that region [19].…”
Section: Introductionmentioning
confidence: 99%